Implementasi Kelas Kimia Tanpa Limbah: Penerapan Eksperimen Kimia Ramah Lingkungan Untuk Meningkatkan Pemahaman Sains Siswa SD di Majalengka - Puspita, Retno Ayu; Astuti, Tiwi Nur; Santika, Gusman; Nabila, Azzahra; Hasmin, Maulina (Andromeda: Jurnal Pengabdian Masyarakat Rafflesia, 2025)
Science education at the primary school level plays a crucial role in forming students' initial scientific understanding. However, chemistry learning is often constrained by limited facilities and concerns about the environmental impact of experiment waste. This community service program aims to address these issues through the implementation of a Zero-Waste Chemistry Class by applying safe, simple, and non-hazardous Green Chemistry-based experiments. The target of this activity was students of SD IT Tazkia Insani in Majalengka Regency. The methods included preparing simple experiment kits and guides (Making Milk Glue), socialization, mentoring, and evaluation using test instruments based on three OECD (2023) science literacy indicators. The program results show that the application of eco-friendly experiments was highly effective in enhancing overall science understanding, with 57.14% of students achieving the Very Good category and 42.86% achieving the Good category. Furthermore, the activity successfully fostered an understanding of eco-friendly chemistry awareness among students, with the Good category dominating (42.86%). This program is expected to be an innovative, meaningful, and sustainable science learning model, aligning with Sustainable Development Goals (SDGs) points 4 (Quality Education) and 12 (Responsible Consumption and Production). Keywords: Zero-Waste Chemistry; Eco-Friendly Experiments; Green Chemistry; Primary School Students; Science Understanding.